If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) + -5(x + -4) = x + 4 + -1(x + -4) Reorder the terms: 4(-5 + x) + -5(x + -4) = x + 4 + -1(x + -4) (-5 * 4 + x * 4) + -5(x + -4) = x + 4 + -1(x + -4) (-20 + 4x) + -5(x + -4) = x + 4 + -1(x + -4) Reorder the terms: -20 + 4x + -5(-4 + x) = x + 4 + -1(x + -4) -20 + 4x + (-4 * -5 + x * -5) = x + 4 + -1(x + -4) -20 + 4x + (20 + -5x) = x + 4 + -1(x + -4) Reorder the terms: -20 + 20 + 4x + -5x = x + 4 + -1(x + -4) Combine like terms: -20 + 20 = 0 0 + 4x + -5x = x + 4 + -1(x + -4) 4x + -5x = x + 4 + -1(x + -4) Combine like terms: 4x + -5x = -1x -1x = x + 4 + -1(x + -4) Reorder the terms: -1x = x + 4 + -1(-4 + x) -1x = x + 4 + (-4 * -1 + x * -1) -1x = x + 4 + (4 + -1x) Reorder the terms: -1x = 4 + 4 + x + -1x Combine like terms: 4 + 4 = 8 -1x = 8 + x + -1x Combine like terms: x + -1x = 0 -1x = 8 + 0 -1x = 8 Solving -1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = -8 Simplifying x = -8
| c=(5/9)(-45) | | 6x+2=4x+44 | | c=(5/9)-45 | | 9x-(6x-5)=29 | | 0.083*(cos(3.46*t))+0.029*(sin(3.46*t))=0 | | P(x)=2x^3-6x^2+4x-12 | | 10r+70+49-r^2=169 | | w+(2)(-2)+3(4)=2 | | 0.083*cos(3.46*t)+0.029*sin(3.46*t)=0 | | 4x+6=-2x+x-19 | | 6x+10*5x+20= | | (2x-24)+(((2x-24)*2)-24)+((((2x-24)*2)-24)*2)-24=0 | | P(x)=2x^4-2x^3+8x^2-8x | | 6x-5-3x=14-5x-3 | | 61.8r+440+6.18(49-r^2)=338*3.14 | | 3(2x+3)=18 | | 45-74d-90-4d+4+4d= | | 5(x-24)=20 | | n^2-165=0 | | 2y^2-3Y^3-6y^2+7y^3= | | 4x+1-3x=5 | | x^2+4=169 | | 2(1+x)=8 | | -5/9=-2v+1/3 | | (x+25)+125=10 | | x-.70=154 | | r^2-10r-50=0 | | 9x-21+7x-3=180 | | (x+5)(x+4)=0 | | 3x+6=y | | 3x+6=2+x | | 2p+3=5p-7 |